2021
DOI: 10.1007/s00049-021-00339-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical cues of Melissococcus plutonius infected honey bee larvae

Abstract: European foulbrood (EFB), caused by Melissococcus plutonius, is a globally distributed bacterial brood disease affecting Apis mellifera larvae. There is some evidence, even if under debate, that spreading of the disease within the colony is prevented by worker bees performing hygienic behaviour, including detection and removal of infected larvae. Olfactory cues (brood pheromones, signature mixtures, diagnostic substances) emitted by infected individuals may play a central role for hygienic bees to initiate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…1 a, b). The average weight of healthy larva that survived the rearing experiment was 130 ± 20 mg (n = 517), in line with previous studies 26 , 40 . Experiments were conducted with a range of distinct genetic lineages with larva sourced from different colonies (Table 2 ).…”
Section: Resultssupporting
confidence: 90%
“…1 a, b). The average weight of healthy larva that survived the rearing experiment was 130 ± 20 mg (n = 517), in line with previous studies 26 , 40 . Experiments were conducted with a range of distinct genetic lineages with larva sourced from different colonies (Table 2 ).…”
Section: Resultssupporting
confidence: 90%
“…Although, different mechanisms of resistance and implicated factors have been discussed in former studies, the most critical factor seems to be the pathogen multiplication time until pupation with a potential clearance of the pathogen and a lag of bacterial toxin release [8,10]. Former studies reported presumably EFB-resistant (or rather tolerant) larvae found in naturally as well as experimentally infected colonies, an observation we also regularly made in our in vitro studies [6][7][8][11][12][13]. These larvae survive pathogen infestation, succeed to pupate (after defecation) and finally emerge as adult workers.…”
Section: Introductionmentioning
confidence: 72%
“…In M. plutonius infections we usually observe diseased larvae with a strong reduction in body weight and cessation of feeding [ 6 , 7 ]. Hence, we were interested in the expression of candidate genes related to feeding behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In honey bees, hygienic behavior is regulated by chemical communication between developing brood and adult nurse bees, where quantitative ( Salvy et al 2001 , Nazzi et al 2004 , Schöning et al 2012 , McAfee et al 2017 , Wagoner et al 2019 , Liendo et al 2021 ) and qualitative ( Kathe et al 2021 , Mondet et al 2021 ) changes of brood odor profiles can signal health status and trigger hygienic uncapping and removal of brood. Of particular interest are cuticular hydrocarbons (CHCs), which form a waxy layer on insect cuticles to prevent desiccation ( Jackson and Baker 1970 , Blomquist et al 1987 ) and facilitate communication, including nestmate recognition ( Howard and Blomquist 2005 , van Zweden and d’Ettorre 2010 ) and task performance ( Greene and Gordon 2003 ).…”
mentioning
confidence: 99%